THE TEACHING OF ENGLISH VOCABULARY TO YOUNG LEARNERS - Lelawati, Setiani; Dhiya, Selma; Mailani, Putri Nurazijah (PROJECT (Professional Journal of English Education), 2018)
This study is aimed to describe the techniques used by the teacher in teaching English vocabulary for young learners in SD Negeri Padasuka 2 in Soreang. The method used in this study is descriptive study. This study was conducted using three techniques of data collection: observation and interview. The source of the data was the English teacher and the subjects were the four grade students of SD Negeri Padasuka 2 Soreang. The findings revealed that the teacher applied various techniques in teaching vocabulary which divided into two stages. For presenting new words, using flashcards and miming are preferred by the teacher in this study. And the final in getting students to practice the words they have learned, the teacher mostly employed identifying and matching the task.Â